2008
DOI: 10.1021/jp075288u
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Aligned Silver Nanorod Arrays Prepared by Oblique Angle Deposition as Surface Enhanced Raman Scattering Substrates

Abstract: Aligned Ag nanorod arrays have been fabricated on glass substrates using an oblique angle vapor deposition (OAD) method. The surface morphology and structure of the Ag rods were studied by scanning electron microscopy, transmission electron microscopy, and X-ray diffraction. Individual nanorods were found to be primarily cylindrical, albeit with irregularly shaped surface protrusions of the rods. The surface enhanced Raman scattering (SERS) response as a function of nanorod length was investigated using trans-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
301
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(312 citation statements)
references
References 58 publications
8
301
1
Order By: Relevance
“…More details on sample preparation can be found elsewhere [7,8]. The morphology of the Ag nano-islands was inspected by scanning electron microscopy [SEM, Fig.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…More details on sample preparation can be found elsewhere [7,8]. The morphology of the Ag nano-islands was inspected by scanning electron microscopy [SEM, Fig.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…[24][25][26][27][28] Other researchers found that multilayer structures of Ag/Au nanostructures on the smooth metallic underlayer exhibited better SERS sensitivity compared to those without metallic underlayer (EF = 5 × 10 8 ). [29][30][31] However, the factor that governs the enhancement for multilayer structures is not very clear. Recently, Misra et al obtained remarkably high SERS sensitivity using a micro-cavity with a radius of several micrometers.…”
Section: Fabrication Of Sensitive Sers Substrates By Gladmentioning
confidence: 99%
“…[33] All the above experiments and those conducted by Driskell et al suggested that the underlayer reflectivity could play an important role in the multilayer SERS substrates. [29] We have investigated in detail the relationship of underlayer reflectivity and the SERS enhancement of Ag nanorod substrates prepared by oblique angle deposition. We use thin films of different materials with different thicknesses as underlayers to modulate the reflectivity systematically.…”
Section: Fabrication Of Sensitive Sers Substrates By Gladmentioning
confidence: 99%
See 2 more Smart Citations